2016
DOI: 10.1177/2158244016644945
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Early Refractive Error on School-Going Chinese Children

Abstract: Refractive error is a common social issue in every walks of human life, and its prevalence recorded the highest among Chinese population, particularly among people living in southern China, Hong Kong, Thailand, Singapore, and Malaysia. Refractive error is the simplest disorder to treat and supposed to cost the effective health care intervention. The present study included 168 Chinese school-going children aged 10 to 12 years; they were selected from different schools of urban Malaysia. It was surprising to see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The prevalence of refractive error differs significantly between boys and girls of different ethnicities. In a cross-sectional study involving 168 10 -12-year-old Chinese school children in Malaysia by Jayaraman et al, refractive error was higher among girls (73.6%) than among boys (58.4%) [33]. Other studies revealed a significant difference in the presence of refractive errors between the two sexes among school children [15][16][17].…”
Section: Discussionmentioning
confidence: 95%
“…The prevalence of refractive error differs significantly between boys and girls of different ethnicities. In a cross-sectional study involving 168 10 -12-year-old Chinese school children in Malaysia by Jayaraman et al, refractive error was higher among girls (73.6%) than among boys (58.4%) [33]. Other studies revealed a significant difference in the presence of refractive errors between the two sexes among school children [15][16][17].…”
Section: Discussionmentioning
confidence: 95%
“…Although this study found refractive error in 36 males and 20 females with a p value of 0.5, the difference between age and genders was not statistically significant. However, a study reported that overall prevalence of refractive errors among school children was higher among girls than boys (73.1% vs. 55.6%, P=0.001), but there is no significant difference in different age groups (P= 0.790) [9,10].…”
Section: Discussionmentioning
confidence: 96%
“…Astigmatism is the commonest type of refractive errors, affecting 14.9% of children worldwide [1] . Previous Malaysian studies have reported varying prevalence rates of astigmatism in children, ranging from 0.6-21.3% [2][3][4][5] . The SEGPAEDS study conducted among preschool children found that astigmatism was the most prevalent type of refractive error (84%) [6] .…”
Section: Introductionmentioning
confidence: 99%